OUTCOMES OF TOTALLY EXTRAPERITONEAL LAPAROSCOPIC REPAIR FOR INGUINAL HERNIA AT HA TINH PROVINCIAL GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
ABSTRACTIntroduction: To describe clinical and paraclinical characteristics and evaluate the outcomes of totally extraperitoneal (TEP) laparoscopic repair for inguinal hernia in 2025.Patients and Methods: A retrospective and prospective study was conducted on 41 patients with inguinal hernia who underwent totally extraperitoneal (TEP) laparoscopic mesh repair at Ha Tinh Provincial General Hospital between January and December 2025.Results: The mean age was 59.8 ± 15.5 years; all patients were male. The predominant symptom was groin swelling (97.6%); ultrasonography identified hernia contents in 90.2% of cases. The mean operative time was 61.8 ± 14.5 minutes. The main intraoperative complication was peritoneal tear (7.3%); early postoperative complications occurred in 9.8%, mainly hematoma and seroma. The mean hospital stay was 6.9 ± 2.7 days. Good early outcomes were achieved in 85.4% of patients; at 6-month follow-up, 6.3% had persistent symptoms (pain, sensory disturbance), with no recurrence observed.Conclusion: Totally extraperitoneal laparoscopic repair is a safe and effective technique for inguinal hernia, associated with low complication rates, favorable early outcomes, and no recurrence during follow-up.
Keywords: Inguinal hernia; totally extraperitoneal repair; laparoscopic mesh repair.